Beta-ketothiolase Deficiency: Case Report - Şahin, Yasin; Aydın, Derya (Fırat University, 2004)
Mitochondrial acetoacetyl-CoA thiolase, is an enzyme in isoleusin catabolism and ketone body metabolism. The name ''beta-ketothiolase deficiency'' is usually used for the defect of this enzyme. This disorder is clinically characterized by ketoasidotic episodes, sometimes accompanied by unconsiousness. In this article, a 14 months-old infant, diagnosed in the first ketoasidotic episode, was reported because of rarity of the disease and we should consider it in the differential diagnosis of ketoasidotic episodes. ©2004, Fırat Üniversitesi, Tıp Fakültesi

Mitokondriyal asetoasetil koenzim A tiyolaz, izolösin katabolizmasında ve keton cisimciği metabolizmasında rol alan bir enzimdir. Eksikliği ''Betaketo tiyolaz eksikliği" diye adlandırılır. Klinik olarak bilinç kaybının eşlik ettiği ketoasidotik epizodlarla karakterizedir. Bu yazıda sunulan 14 aylık erkek hasta, ilk ketoasidotik atağı sırasında tanı almıştır. Vaka nadir görülmesi ve ketoasidotik atakların ayırıcı tanısında akılda bulundurulması gerektiği için sunulmuştur. ©2004, Fırat Üniversitesi, Tıp Fakültesi
Beta-ketotiyolaz Eksikliği: Vaka Sunumu